ANISOTROPIC VISCOSITY OF THE ANOMALOUS MANTLE - Grachev A.F.; Malevskiy A.B. (My University, 1988)
Anomalous mantle is a characteristic feature of all continental and oceanic rifts at depth, and of zones of intraplate tectonomagmatic activity. An investigation of a standard collection of xenoliths from spinel lherzolite in basalts of the Baikal Rift and central Europe indicates that zones of partial melting occupy as much as 10 percent or, in some less common cases, 15 percent of the total volume of the rock. The following two facts are important for purposes of understanding the rheological properties of the anomalous mantle: (1) zones of partial melting are wide spread in those spinel lherzolites that have experienced strong deformation and have porphyroclastic and lathlike structures; (2) the zones of partial melting, consisting of stringers up to 2 mm thick, are oriented parallel to the long axes of the xenoliths, i.e., along the planes of flattening of such specimens.